2010
DOI: 10.1097/qai.0b013e3181b3552a
|View full text |Cite
|
Sign up to set email alerts
|

HIV Prevalence and Risk Behaviors Among Male Clients of Female Sex Workers in Yunnan, China

Abstract: Objectives To assess the prevalence and risk factors of HIV among male clients of female sex workers in China. Methods Convenience sampling methods were used to recruit 315 clients using FSW-client and client-client networks. Subjects provided information on socio-demographic characteristics and sexual and drug behavior patterns. Blood samples were collected for HIV testing and urine samples for opiate testing. Results Overall HIV prevalence was 6.0%; among drug users it was 30.8%. 33.7% of respondents rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
58
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 11 publications
10
58
4
Order By: Relevance
“…Linkages between research, programmatic interventions, health services, and scale-up of successful pilots are urgently needed. Condom use rates of clients with FSW have been reported to be quite low (Jin et al, 2010;Parish et al, 2003), likely because social norms largely do not support their use. Many FSW may also hesitate to access health services even at specially tailored clinics due to stigma and confidentiality concerns (Wong & Wang, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Linkages between research, programmatic interventions, health services, and scale-up of successful pilots are urgently needed. Condom use rates of clients with FSW have been reported to be quite low (Jin et al, 2010;Parish et al, 2003), likely because social norms largely do not support their use. Many FSW may also hesitate to access health services even at specially tailored clinics due to stigma and confidentiality concerns (Wong & Wang, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in 1996, Wu and colleagues found that nearly 20% of their study participants and 25% of the Jingpo minority in the study area had used drugs [21]. A recently reported study among male clients of female sex workers (FSWs) in the same province found that drug use was prevalent and significantly associated with HIV infection [7]. These observations indicate that drug use remains prevalent among males and rural ethnic minorities, especially the Jingpo minority in Yunnan, and continues to be an important driver of the HIV/AIDS epidemic in this region.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although the Dai and Jingpo minorities, respectively, constitute only 0.3 and 2.5% of Yunnan's population, they account for 7 and 9% of all new HIV infections [4]. Since these HIV prevalence rates are primarily derived from high-risk groups such as IDUs [5][6][7], little is known about the epidemic in the ''general population'' (especially in the Dai and Jingpo minority communities). These studies can provide only a limited understanding of HIV transmission since an individual's probability of infection or transmission is influenced by his/her position in social or behavioral networks [8], while the risk of epidemic at the population-level is influenced by network structures [9].…”
Section: Introductionmentioning
confidence: 99%
“…While HIV prevalence among FSWs remains below 1% in Chinese Centers for Disease Control and Prevention (CDC) sentinel sites, FSW biomarker studies in selected locales have found HIV prevalence up to 8% and estimates of STIs up to 91% (Xu et al 2008). Studies among FSWs' clients have found HIV prevalence up to 6% and STI prevalence up to 23% (Xu et al 2008, Jin et al 2010, Rou et al 2010, Yang et al 2010b). Our 2006 nationally representative data on men's self-reported FSW contact and STIs were consistent with these reports, demonstrating that 6% to 8% of men buy commercial sex and that unprotected commercial sex increased the likelihood of contracting STIs (Pan et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Our 2006 nationally representative data on men's self-reported FSW contact and STIs were consistent with these reports, demonstrating that 6% to 8% of men buy commercial sex and that unprotected commercial sex increased the likelihood of contracting STIs (Pan et al , 2011. Extensive FSW use by Chinese men from all social classes and the high prevalence of STIs among FSWs (Wang et al 2007, Xu et al 2008, Jin et al 2010) raises concern about the spread of STIs/HIV, especially in male clients, who are proving to be an important bridge population.…”
Section: Introductionmentioning
confidence: 99%